Corn Ice Cream Making Training For PKK Cadres To Cultivate An Entrepreneurial Spirit In Bluri Solokuro Lamongan - Pusvyta Sari; Dymas Yulia Putri Kusumaningtyas; Ade Rizki Verdiansyah; Kurnia Sari; Nurul Akromah; Muhammad Khowiluddin (LPPM, STAI Al-Azhar Menganti, 2024)
Community service based on Kuliah Kerja Nyata (KKN), Institut Pesantren Sunan Drajat Lamongan 2023 held in Bluri Village, Solokuro, Lamongan. Training on making ice cream from corn was held by the KKN group for Family Welfare Empowerment (PKK) cadres. This activity aims to optimize the potential of corn, as an abundant agricultural product in Bluri village, so that it has higher economic value, and provide entrepreneurial insight. The service method used is Participatory Action Research (PAR). The results of this activity are the delivery of material on processing corn into ice cream and entrepreneurial insight regarding processed corn products that have economic value to improve the community's economy. The impact is the growing interest of PKK cadres in using corn to make ice cream and increasing insight into entrepreneurship by optimizing the potential of agricultural products in Bluri village.